Augustin Legrand, un pionnier inconnu du livre jeunesse - Jacques Desse (Strenae, 2016)
This article focuses on Augustin Legrand, a 19th century engraver, illustrator, author, and publisher who devoted himself almost exclusively to children's publications and was one of the first designers of animated children’s books. After presenting the scarce biographical data (mainly professional) available on his persona, this paper will present characteristics of his children’s works and conclude with a bibliography.